Cleidocranial dysplasia and novel RUNX2 variants: dental, craniofacial, and osseous manifestations (Journal of Applied Oral Science, 2022)
Cleidocranial dysplasia (CCD) is a skeletal disorder affecting cranial sutures, teeth, and clavicles, and is associated with the RUNX2 mutations. Although numerous patients have been described, a direct genotype–phenotype correlation for RUNX2 has been difficult to establish. Further cases must be studied to understand the clinical and genetic spectra of CCD. Objectives: To characterize detailed phenotypes and identify variants causing CCD in five unrelated patients and their family members. Methodology: Clinical and radiographic examinations were performed. Genetic variants were identified by exome and Sanger sequencing, data were analyzed by bioinformatics tools. Results: Three cases were sporadic and two were familial. Exome sequencing successfully detected the heterozygous pathogenic RUNX2 variants in all affected individuals. Three were novel, comprising a frameshift c.739delA (p.(Ser247Valfs*)) in exon 6 (Patient-1), a nonsense c.901C>T (p.(Gln301*)) in exon 7 (Patient-2 and affected mother), and a nonsense c.1081C>T (p.(Gln361*)) in exon 8 (Patient-3). Two previously reported variants were missense: the c.673C>T (p.(Arg225Trp)) (Patient-4) and c.674G>A (p.(Arg225Gln)) (Patient-5) in exon 5 within the Runt homology domain. Patient-1, Patient-2, and Patient-4 with permanent dentition had thirty, nineteen, and twenty unerupted teeth, respectively; whereas Patient-3 and Patient-5, with deciduous dentition, had normally developed teeth. All patients exhibited typical CCD features, but the following uncommon/unreported phenotypes were observed: left fourth ray brachymetatarsia (Patient-1), normal clavicles (Patient-2 and affected mother), phalangeal malformations (Patient-3), and normal primary dentition (Patient-3, Patient-5). Conclusions: The study shows that exome sequencing is effective to detect mutation across ethnics. The two p.Arg225 variants confirm that the Runt homology domain is vital for RUNX2 function. Here, we report a new CCD feature, unilateral brachymetatarsia, and three novel truncating variants, expanding the phenotypic and genotypic spectra of RUNX2 , as well as show that the CCD patients can have normal deciduous teeth, but must be monitored for permanent teeth anomalies.